Arithmetic Guides and Matrices in the Holy Qura’an - Amel Nashat Shakir; Nada S. Abdulmajeed; Dr. Ahmed Fatih Omer (Genius Journals, 2022)
The development of computers and its tools have led to the development of more specialized and in-depth research and studies in the Noble Qur’an and its sciences, especially those that research the scientific aspect of its miracles. The development, diversity and expansion of modern sciences, especially mathematics and engineering cause the sciences of the Holy Qur’an to expand in line with these sciences. Each verse of the enlightening Qur’an spreads two sets of lights, the light of its guidance and the light of its miracles. Every group of people according to their degrees takes their fortune from any sign or scene from the scenes of the Qur’an. In this study, we noticed that the Noble Qur’an mentioned accounting and geometry and its divisions, including numbers, digits and matrices, the importance of numbers and digits and its dealings with modern mathematics. We find that modern mathematics is currently based on the digit in its complete and special form, and not on numbers. Thus, we find in our studies rational numbers which are fractions. There are also irrational numbers which are very complex in form in addition to Catrinian numbers etc. Because of the importance of the matrix, we believe that the Qur’an refers to it through a group of Qur’anic references, the most important of which was the mention of the word “masfuf” which can be translated into matrix in two generous verses. It is particularly mentioned in the two great surahs with names bearing the meaning of the row (As-Saaffat and As-Saff). It is considered a major basis in many branches of science and research, especially mathematics and modern sciences, such as computer and its applications. It depends on it in its design principle and in its work in programming and programs. The matrix is considered the basic structure for the data in the most important scientific engineering programming for research and development until now which is Matlab program. It appears through the study that the contents of the Noble Qur’an of words, letters and numbers can be described in the form of various matrices, and since the verses of the Noble Qur’an are written and lined up in rows, the line matrix is the appropriate form to deal with the contents of the Holy Qur’an, whether literal or numerical. Thus, it is possible to perform several mathematical and logical operations on them. The Qur’anic reference to matrices is a precursor to the Qur’an and a scientific miracle that is added to the miraculous balance of this glorious book. The line matrix or the line ray can be considered the basic mathematical structure of the Qur’anic data, especially the numerical data
Keywords: Numbers and digits in the Holy Qur’an; basic Qur’an numerical data; scientific miracles of mathematics in the Holy Qur’an; matrices in the Holy Qur’an